Integrate in-game entertainment activities into non-game applications: Explore gamification in loyalty activities to increase consumer loyalty in e-commerce within the scope of Metro Manila - Abella, Jeremy Ryan G. (Animo Repository, 2023)
This research analysis was conducted to examine the influence of gamified loyalty programs on customer satisfaction and purchase intention among Shopee users in Metro Manila, with intrinsic motivation as a moderating variable, and its indirect impact on customer loyalty. Data was collected from a minimum of 200 respondents using purposive sampling through online survey questionnaires developed on Google Forms. The findings indicate a positive correlation between the variables. Additionally, the results suggest that while gamified loyalty programs have an impact on customer satisfaction, they do not significantly affect purchase intention. Furthermore, intrinsic motivation was not found to have a significant moderating effect between gamified loyalty programs and customer satisfaction or purchase intention. The researchers recommend that Shopee introduce novel forms of gamified loyalty programs to enhance customer satisfaction and purchase intention. The researchers propose using innovative and interactive game mechanics to keep customers engaged and returning, as well as customizing the gamification experience for each user by utilizing customer data to provide targeted challenges and rewards. Finally, continuous monitoring and analysis of customer engagement and conversion rates can aid Shopee in optimizing and refining the gamification experience over time.